Assessment of Raised Alanine Aminotransferase (ALT) and its Relation with Antibiotic Resistance in Enteric Fever Among Children - Hussain, Irshad; Wahid, Sughra; Qureshi, Maliha Akhtar; Hashmi, Fasih Ul (Pakistan Armed Forces Medical Journal, 2022)
Objective: To study the abnormality of alanine aminotransferase (ALT) in enteric fever among children and to test the association between raised alanine aminotransferase with antibiotics resistance.Study Design: A descriptive prospective study.Place and Duration of Study: This study was conducted at the Pediatric department of KRL Hospital, Islamabad from October 2018 to March 2020.Material and Methods: A total of 100 patients were enrolled as per inclusion criteria. Detailed clinical history was taken and physical examination was done. Laboratory tests i.e. full blood count, liver function tests and blood culture were performed to validate the inclusion, exclusion criteria and to collect the data of required variables mentioned in structured proforma.Results: Out of 100 culture-proven typhoid fever patients, 57% were male and 43% female. The average age was 7.79 ± 3.3 years. Raised alanine aminotransferase (>45 U/l) was observed in 60%. The alanine aminotransferase is raised in at least 51% of the population having typhoid fever with p-value 0.035. The results also showed that the proportion of extensive drug resistant (XDR) typhoid is greater in the patients having raised alanine aminotransferase as compared to the patients having normal alanine aminotransferase with p-value 0.003.Conclusion: On the basis of our study, we concluded that high alanine aminotransferase is related with enteric fever. We also observed that those having raised alanine aminotransferase have more chances of extensive drug resistant typhoid.